Pituitary dysfunction induced by immune checkpoint inhibitors is associated with better overall survival in both malignant melanoma and non-small cell lung carcinoma: a prospective study. Issue 2 (30th June 2020) - Kobayashi, Tomoko; Iwama, Shintaro; Yasuda, Yoshinori; Okada, Norio; Okuji, Takayuki; Ito, Masaaki; Onoue, Takeshi; Goto, Motomitsu; Sugiyama, Mariko; Tsunekawa, Taku; Takagi, Hiroshi; Hagiwara, Daisuke; et al.
Abstract : Background: Several immune-related adverse events (irAEs) are reported to be associated with therapeutic efficacy of immune checkpoint inhibitors, yet whether pituitary dysfunction, a life-threatening irAE, affects overall survival (OS) in patients with malignancies is unclear. This prospective study examined the association of pituitary dysfunction (pituitary-irAE) with OS of patients with non-small cell lung carcinoma (NSCLC) or malignant melanoma (MM). Methods: A total of 174 patients (NSCLC, 108; MM, 66) treated with ipilimumab, nivolumab, pembrolizumab, or atezolizumab at Nagoya University Hospital were evaluated for OS and the development of pituitary-irAE. Kaplan-Meier curves of OS as a function of the development of pituitary-irAE were produced with the log-rank test as a primary endpoint. Results: Pituitary-irAE was observed in 16 patients (4 (3.7%) with NSCLC, 12 (18.2%) with MM) having two different disease types: hypophysitis with deficiency of multiple anterior pituitary hormones accompanied by pituitary enlargement, and isolated adrenocorticotropic hormone (ACTH) deficiency without pituitary enlargement. Among these patients, 6 developed pituitary-irAE while being treated with ipilimumab (6/25 patients (24.0%) treated with ipilimumab) and 10 developed pituitary-irAE during treatment with nivolumab or pembrolizumab (10/167 (6.0%)). All 16 patients had ACTH deficiency and were treated with physiological doses of hydrocortisone. The development of pituitary-irAE was associated with better OS in patients with NSCLC (not reached vs 441 (95% CI not calculated) days, p<0.05) and MM (885 (95% CI 434 to 1336) vs 298 (95% CI 84 to 512) days, p<0.05). Conclusions: In our study cohort, the incidence of pituitary-irAE was higher than previously reported and the development of pituitary-irAE predicted better prognosis for both NSCLC and MM when patients were treated with physiological doses of hydrocortisone. Clinical trials registration: UMIN000019024.